Cultivating Children’s Social Awareness in the Multicultural and Diverse Community: A Perspective from Empathetic Teaching - Popi Rosepti (Edueksos : Jurnal Pendidikan Sosial dan Ekonomi, 2022)
Abstract: The multicultural and social diversity urge children to build social awareness skill which drives them to consciously aware of specific range of social experience from a specific point of view. In educational setting, this becomes a concern because children spur into cultural diversity in their daily life so that teachers take a role to facilitate them with the ability to adapt with the situation. One of the ways in meeting the issue is through implementing empathetic teaching which is a concept of teachers showing their compassion to students. Therefore, the main framework of this study is to elaborate the concept and investigate further how empathetic teaching can allow teachers to cultivate social awareness to their students in the perception year. The originality of the paper lies in offering a conceptual framework of empathetic teaching through mapping the main relevant literatures and identifying and engaging with the central theoretical issues while suggesting a perceptual framing of classroom setting in childhood education. By analyzing the data using content analysis, the findings reveal that empathetic teaching practiced by teachers can be beneficial to build children’s social awareness through having good perception on their exposure to the surrounding. This also allows them to have an ability to adapt in the diverse community by appreciating differences to promote a social peaceful life in this contemporary world.Keywords: Social awareness; Multicultural; Diverse community;  Empathetic Teaching; Childhood Education Abstrak: Keberagaman social dan budaya menuntut anak mengembangkan kepedulian sosial mereka. Hal ini akan mengarahkan mereka pada kesadaran dalam memahami situasi tertentu dalam kehidupan social dengan menggunakan sudut padang yang baik. Dalam konsep pengajaran, kepedulian sosial ini berperan penting karena anak-anak berada dalam lingkungan dimana keseharian mereka dihadapkan dengan kehidupan sosial yang beragam. Maka, guru perlu mengambil peran untuk memfasilitasi mereka dengan kemampuan adaptasi pada kondisi tersebut. Salah satu caranya yakni dengan menerapkan konsep pengajaran empati, yakni sebuah konsep yang mengajarkan para guru untuk meunjukkan rasa empati mereka kepada murid. Kerangka utama dalam penelitian ini adalah menjabarkan konsep tersebut dan menelaah lebih dalam bagaimana pengajaran empati dapat membantu guru menanamkan kepeduluan sosial kepada murid. Penelitian ini merupakan kajian melalui kumpulan sumber tulisan yang sesuai dengan topik pengajaran empati, lalu diidentifikasi, dan dikaitkan dengan konsep kepedulian social pada anak. Teknik Analisa data yang digunakan adalah ‘content analysis’ yang menghasilkan sebuah gambaran bahwa pengajaran empati yang dilakukan oleh guru di dalam kelas akan menjadi media dalam mengembangkan kepedulian sosial anak melalui pembentukan pola pikir yang baik terhadap lingkungan di sekitar mereka. Selain itu, pengajaran empati membantu anak memiliki kemampuan adaptasi dalam menghadapi keberagaman sosial dengan memiliki kemampuan menghargai akan setiap perbedaan yang ditemukan. Kepedulian sosial ini penting ditanamkan sebagai bekal dalam menciptakan kehidupan sosial yang damai di dunia kontemporer ini.Kata Kunci: Kepedulian Sosial; Multikulturalisme; Keberagaman sosial; Pengajaran Empati; Pendidikan Anak.